Efficacy and safety of open-label etanercept on extended oligoarticular juvenile idiopathic arthritis, enthesitis-related arthritis and psoriatic arthritis: part 1 (week 12) of the CLIPPER study. Issue 6 (21st May 2013) - Horneff, Gerd; Burgos-Vargas, Ruben; Constantin, Tamas; Foeldvari, Ivan; Vojinovic, Jelena; Chasnyk, Vyacheslav G; Dehoorne, Joke; Panaviene, Violeta; Susic, Gordana; Stanevica, Valda; Kobusinska, Katarzyna; Zuber, Zbigniew; et al.
Abstract : Objective: To investigate the efficacy and safety of etanercept (ETN) in paediatric subjects with extended oligoarticular juvenile idiopathic arthritis (eoJIA), enthesitis-related arthritis (ERA), or psoriatic arthritis (PsA). Methods: CLIPPER is an ongoing, Phase 3b, open-label, multicentre study; the 12-week (Part 1) data are reported here. Subjects with eoJIA (2–17 years), ERA (12–17 years), or PsA (12–17 years) received ETN 0.8 mg/kg once weekly (maximum 50 mg). Primary endpoint was the percentage of subjects achieving JIA American College of Rheumatology (ACR) 30 criteria at week 12; secondary outcomes included JIA ACR 50/70/90 and inactive disease. Results: 122/127 (96.1%) subjects completed the study (mean age 11.7 years). JIA ACR 30 (95% CI) was achieved by 88.6% (81.6% to 93.6%) of subjects overall; 89.7% (78.8% to 96.1%) with eoJIA, 83.3% (67.2% to 93.6%) with ERA and 93.1% (77.2% to 99.2%) with PsA. For eoJIA, ERA, or PsA categories, the ORs of ETN vs the historical placebo data were 26.2, 15.1 and 40.7, respectively. Overall JIA ACR 50, 70, 90 and inactive disease were achieved by 81.1, 61.5, 29.8 and 12.1%, respectively. Treatment-emergent adverse events (AEs), infections, and serious AEs, were reported in 45 (35.4%), 58 (45.7%), and 4 (3.1%), subjects, respectively. Serious AEs were one case each of abdominal pain, bronchopneumonia, gastroenteritis and pyelocystitis. One subject reported herpes zoster and another varicella. No differences in safety were observed across the JIA categories. Conclusions: ETN treatment for 12 weeks was effective and well tolerated in paediatric subjects with eoJIA, ERA and PsA, with no unexpected safety findings.